Biological treatment of a brominated micropollutant α-hexabromocyclododecane (α-HBCDD) from a raw hospital wastewater - Delia Teresa Sponzax; Gökçe Güney (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
The brominated micropollutants were not removed with conventional biological treatment processes. In this study it was aimed to treat the α-HBCDD which is a hydrophobic organic substance using a sequential treatment process consisting from an upflow anaerobic batch reactor (UASB) and a completely stirred tank reactor (CSTR) since α-HBCDD is a hydrophobic brominated micropollutant and its removals was very low under long retention times in anaerobic sediments (in monitored natural attenuation environments) and under aerobic stimulated environments (in conditions adding limiting nutrient and electron acceptors for support the microorganisms growth), separately, a sequential anaerobic/aerobic reactor system proses was choosen. The anaerobic and aerobic removals of α-HBCDD were 7% and 12%, respectively, at a SRT of 55 days. The effects of SRTs on α-HBCDD and its metabolite removals was investigated. The yields increased as the SRT was increased from 5 days up to 55 days. The total α-HBCDD yields in the whole sequential biological system was recorded as 18,3%. The metabolite of α-HBCDD is α2-Bromocyclododecan-1-ol (2-BCD). This metabolite was produced under anaerobic conditions and it was removed in aerobic reactor with a yield of 17% at 55 days SRT. The maximum 2-BCD removal efficiency was 63,6% in the sequential reactor process.